Managing sport and leisure facilities : a guide to competitive tendering - Sayers, Philip (E. & F.N. Spon, 1991)
S1ncise and thoroughly detailed Managing Sport and Leisure Facilities is a clean operating guide to leisure management by contract, providing expert advice for both contractor and client. The author includes extracts from the relevant.